The mechanism of immune related signal pathway Egr2-FasL-Fas in transcription regulation and methylated modification of Paralichthys olivaceus under acute hypoxia stress. Issue 123 (April 2022) - Liu, Binghua; Li, Guangling; Yang, Jun; Li, Xiaohui; Wang, Hao; Yang, Jing; Wen, Haishen; He, Feng
Abstract: Apoptosis genes Egr2, Fas and FasL are related to immune responses. However, the mechanism of these genes inducing apoptosis in fish are still not very clear. An acute hypoxia treatment (1.73 ± 0.06 mg/L) for 24 h was carried out on Japanese flounder ( Paralichthys olivaceus ). The increasingly dense apoptotic signals at 3 h, 6 h, 12 h by TUNEL in skeletal muscle indicated that hypoxia could quickly affect muscle growth and development. Furthermore, we concluded that the Egr2-FasL-Fas signal pathway, which was located at the upstream of apoptotic executor protein caspases, was related to the apoptosis by quantitative real-time PCR, protein concentration detection in ELISA and double gene in situ hybridization methods. The mechanism of the pathway was researched in transcription regulation and epigenetic modification by dual-luciferase reporter assay and bisulfite modified method, respectively. Egr2, as a transcription factor, could up-regulate the expression of FasL gene. And its binding site was mainly between −479 to −1 of FasL gene promoter. The 5th CpG dinucleotides (−514) methylation levels in FasL gene were significantly affected by hypoxia, and they were negatively correlated with its expressions. These suggested that the −514 site may be a very important site to regulate the FasL gene expression. Above results, we concluded that hypoxia activated the immune related signal pathway Egr2-FasL-Fas to induced skeletal muscle apoptosis to affect growth and development of Japanese flounder. The study revealed the mechanism of hypoxia induced apoptosis, which could provide a reference for fish immunity and aquaculture management. Highlights: Skeletal muscle cell immune response was activated by acute hypoxia stress. The immunity was related to Egr2-FasL-Fas signal pathway to induce apoptosis. Egr2 transcriptionally regulated the expression of FasL gene. Hypoxia acts on the signal pathway by epigenetic modification.